THE IMPACT OF SERVICESCAPE AND SERVICE QUALITY TO COSTUMER SATISFACTION (STUDY IN WISATA MUSEUM ANGKUT BATU, JAWA TIMUR) - Syawaludin, Azhari (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study disscuses the servicescape and service quality that affect customer satisfaction tourism service. The purpose of this study was to determine whether the servicescape factors consisting of enviromental conditions, spatial layout, signs and symbol or artifacts and service quality factors consisting of tangibles,  reliability,  responsiveness,  assurance,  and  emphaty affects  customer satisfaction and also to find out which factors are the most dominant influence on custumer satisfaction. The analytical method used is multiple regression analysis and classical assumption. As for testing the hypothesis using the F test and t test.Based on the analysis performed, variable servicescape (X1) and service quality (X2) are jointly have a significant impact on customer satisfaction. Based on the t test is known that servicescape (X1) and service quality (X2) have significant effect partially. Through standardized β coefficient obtained that variable service quality (X2) factor consisting of tangibles have a dominant influence of customer satisfaction in wisata Museum Angkut Batu, Jawa Timur.  Keywords : Servicescape (X1), Service quality(X2), Costumer Satisfaction (Y).